Policy Learning and Handling of Covid-19 in Indonesia - Leo Agustino (Institut Pemerintahan Dalam Negeri, 2021)
Abstract This article discusses the policy learning process in managing the Coronavirus Disease 2019 (COVID-19) within Indonesia and asks several questions regarding the policies formulated and implemented, as well as how the government